Edukasi Dan Pelatihan Dapat Meningkatkan Pengetahuan, Sikap dan Praktik Penggunaan Alat Pelindung Diri Pada Kelompok Wanita Nelayan Di Wilayah Pesisir Maccini Baji Kabupaten Pangkep - Yusriani Yusriani; Ernaningsih Ernaningsih; Muhammad Khidri Alwi (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Workers in the informal sector, especially women fishing groups in the coastal area of Maccini Baji, often work in an unfavorable environment and neglect occupational health/safety due to weak capital and lack of knowledge about the use of personal protective equipment. Whereas workers' health is a development asset that should be protected and cared for. Community service, especially the Women Fishermen Group in the coastal area of Maccini Baji, stems from the problem of the high incidence of skin diseases. Factors that influence the high prevalence of skin diseases are inadequate knowledge, attitudes and practices of using Personal Protective Equipment. Education and training are solutions that are agreed with the community in an effort to increase knowledge, attitudes and skills regarding the use and distribution of personal protective equipment. To observe and evaluate the knowledge, attitudes and abilities of the Women Fishermen Group using a pre-post test questionnaire, and a skill checklist both before and after education and training. The results of the activity showed that there was an increase in the knowledge, attitude and practice of the Women Fishermen Group about the importance of using Personal Protective Equipment.